Mechanism and Control of Roadway Floor Rock Burst Induced by High Horizontal Stress. (5th July 2021) - Guo, Dongming; Kang, Xinchao; Lu, Zhiying; Chen, Qiyu
Abstract : According to the characteristics of rock burst of high horizontal stress roadway floor, the rock burst mechanism of roadway floor was studied with the background of south track roadway Xing'an mine. Based on the deflection theory and energy principle of the slab, the mechanical model of the floor of the roadway under high horizontal stress was established, the stress and energy criteria of rock burst occurred in the floor of the roadway were deduced, the prevention and control measures of the floor pressure relief with large diameter borehole and concrete-filled steel tube pile support were put forward, and the key parameters were determined. By establishing a numerical model, the evolution law of plastic zone, horizontal stress, and elastic strain energy density of roadway floor with or without support is contrastively analyzed. The results show that the effective means to prevent and control the floor rock burst is to cut off the stress transfer path by weakening the hard floor to reduce floor energy accumulation so as to reduce the floor rock burst risk. Based on the above research, field tests were carried out, and the microseismic monitoring results showed that the floor pressure relief of large diameter boreholes and concrete-filled steel tube pile support effectively relieved the floor rock burst and guaranteed the safety and efficiency of roadway excavation. This technology can provide a reference for the prevention and control of floor rock burst of similar roadways.